2016
DOI: 10.1111/1346-8138.13570
|View full text |Cite
|
Sign up to set email alerts
|

Ungual hyalohyphomycosis caused by Fusarium proliferatum in an immunocompetent patient

Abstract: The patient was a 73-year-old healthy female farmer who had been treated with terbinafine for 25.5 months by a primary physician. She exhibited a discoloration and thickening of the right big toenail. She had no concomitant paronychia. Direct microscopy revealed chlamydoconidia and hyphae, and periodic acid-Schiff stained nail specimen showed septate hyphae. On the basis of these morphological features and gene analysis, the final diagnosis was ungual hyalohyphomycosis caused by Fusarium proliferatum. Topical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…By analogy with paper, we carried out a study using direct microscopy, further cultured and identified the isolate morphologically and by PCR as for F. proliferatum . Direct microscopy revealed chlamydioconidia and hyphae in the same way as in the paper [ 36 ]. The isolate had typical morphological properties.…”
Section: Resultssupporting
confidence: 60%
“…By analogy with paper, we carried out a study using direct microscopy, further cultured and identified the isolate morphologically and by PCR as for F. proliferatum . Direct microscopy revealed chlamydioconidia and hyphae in the same way as in the paper [ 36 ]. The isolate had typical morphological properties.…”
Section: Resultssupporting
confidence: 60%
“…An amphotericin B solution (2.0 mg/mL in a 1:1 mixture of DSMO and isopropyl alcohol) was applied in Switzerland 11 . In Japan, five patients were successfully treated with antifungals (itraconazole, n = 2; efinaconazole, n = 2; voriconazole, n = 1), and the proportion of patients cured with antifungals was 29.4% (5/17 cases) 12 . The MIC of efinaconazole against Fusarium species is lower than that of itraconazole 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…11 In Japan, five patients were successfully treated with antifungals (itraconazole, n = 2; efinaconazole, n = 2; voriconazole, n = 1), and the proportion of patients cured with antifungals was 29.4% (5/17 cases). 12 The MIC of efinaconazole against Fusarium species is lower than that of itraconazole. 10,13 Moreover, efinaconazole shows a broad spectrum of antifungal activities and is expected to be effective for nondermatophyte onychomycosis due to Candida, Aspergillus, and Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium petroliphilum and F. keratoplasticum are found in environments and cause invasive pulmonary infection or sinusitis in immunocompromised patients, which may disseminate to other organs and causes sepsis (7,8). FSSC members degrade keratin, with lower ability than dermato phytes (9), and cause superficial cutaneous inflammation (10).…”
Section: Discussionmentioning
confidence: 99%